THE QUALITY OF AIR IN HOSPITAL ENVIRONMENTS CLIMATIZED AND ITS INFLUENCE IN THE OCCURRENCE OF INFECTIONS - Patrícia Staciarini Anders; Marinésia Aparecida do Prado; Adenícia Custódia Silva e Souza; Anaclara Ferreira Veiga Tipple; May Socorro Martinez Afonso (Universidade Federal de Goias, 2004)
Climatized environment is defined as the environment where temperature and humidity are controlled.We have made a review of literature, from 1990 to 2001, through data base MEDLINE, LILACS and Ministry ofHealth Brazil. The aim of this study was to analyze the air quality in climatized environment and the last as a riskfactor for hospital infection HI. Twenty-three articles where analyzed and gathered by the focused theme;patterns and principles for maintaining the air quality; air quality and isolation of microorganism; air quality andoccurrence of infection. The standard of quality quotes: ventilation, maintenance and cleanness of climatizationsystems. Aspergillus, Legionella, Acinetobacter, Clostridium, Nocardia, among others where found in airconditioned devices and the first three ones being responsable for booms of HI.